Measurement of Thermal Comfort at Working Environment in Manufacturing Industry - Isa, Halim; Adi , Saptari; Seri Rahayu , Kamat; Rohana, Abdullah; Nor Akramin, Mohamad (2007)
Thermal comfort was identified as one of significant contributors to safe working environment. Specifically, thermal comfort is defined as condition of mind that expresses satisfaction with complex thermal factors. The objectives of the study are to determine the perceptions of workers regarding to thermal comfort in their working environment and to obtain the level of thermal comfort at working environment in Malaysian manufacturing industry. A case study was carried-out in a manufacturing company situated in Selangor, Malaysia. Direct technical measurement technique associated with a thermal comfort monitor (QUEST ™) was utilized to measure thermal comfort quantities such as air temperature, radiant temperature, relative humidity and air velocity in the working environment. The captured thermal comfort quantities are then interpreted using QuestSuite Professional Software to obtain the values of the votes of a large group of worker and percentage of thermally dissatisfied worker, which is expressed in Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD) respectively. Based on obtained results, work area for Fluidity Testing was identified in thermally stress associated with warm condition as indicated by average PMV and PPD of 2.0 and 79% respectively. Other work areas were identified in slightly warm working environment as they reached PMV less than 1.6 and PPD about 50%. In addition, there is no work area in the case study represents acceptable thermal comfort. Based on the results obtained, it can be concluded that the workers experienced thermal discomfort associated with warm working environment. As a consequence, they were dissatisfied with the current thermal condition in their working environment.